AB1339-HPR SAFETY AND ADHERENCE OF THE JAK INHIBITORS IN CLINICAL PRACTICE IN RHEUMATOID ARTHRITIS. (2nd June 2020) - Valero, C.; Calvo Garcia, A.; García Castañeda, N.; Ortiz, A.; Llorente, I.; Varas, B.; Castañeda, S.; Garcia de Vicuna, R.; Ramirez, E.
Abstract : Background: The Janus Kinase (JAKi) inhibitors Baricitinib (BAR) and Tofacitinib (TOF) are indicated for moderate to severe active rheumatoid arthritis (RA). Data about safety, effectiveness in refractory patients and adherence in real clinical practice in our population are scarce. Objectives: An evaluation of safety, adherence and reasons to consider suspension of JAKi in routine clinical practice. Methods: Retrospective observational study of patients with RA treated with BAR and TOF according to usual clinical practice between September 2017 - December 2019. Data were collected from the electronic medical record and from the Dominion® Outpatient Drug Dispensing program. Demographic, clinical, laboratory and treatment-related variables were collected, including reasons for discontinuing JAKi (inefficiency and toxicity). Adherence was calculated using the Compliance Questionnaire on Rheumatology (CQR-5), and the average possession ratio (RMP), which is defined as the number of days with treatment dispensed between the total days of the period analyzed, considering the adherent patient when RMP had a ≥ 0.8. Laboratory abnormalities were defined according to normal limit values (NLV) and specifications of data sheet. A descriptive analysis was performed using proportions, medians and interquartile ranges (IQR) using the SPSS v.15 program. Results: Thirty patients were included in treatment with BAR and nine with TOF. The median age was 62.9 (RIQ 49.9-74.4), 34 (87.2%) were women, 28 (71.2%) anti-CCP and 32 (82.1%) were rheumatoid factor positive, with erosive disease in 34 (87, 2%) patients. In the previous treatment, 9 (23.1%) were naive to biological, 6 (15.4%) had received 1 biological, 18 (46.1%) 2 biologicals, and 6 (15.4%) ≥ 3 biologicals. The median treatment time was 8.4 months (RIQ 6.5-20.3) in BAR and 13.2 (RIQ 3.9-20.7) in TOF. The reasons for consider suspension shown in Table 1 . Conclusion: In our population, mostly refractory to biological, more than half of the patients maintain treatment with JAKi, with optimal adherence. The main reason for the suspension of both drugs was inefficiency. The most frequent adverse effects were hypercholesterolemia in both groups and infections in BAR, with a high frequency of herpes zoster. No cardiovascular or thromboembolic events were observed. Disclosure of Interests: Cristina Valero: None declared, Alberto Calvo Garcia: None declared, Noelia García Castañeda: None declared, Ana Ortiz: None declared, Irene Llorente Speakers bureau: Gebro, Janssen, Sanofi, Lilly., Blanca Varas: None declared, Santos Castañeda: None declared, Rosario Garcia de Vicuna Grant/research support from: BMS, Lilly, MSD, Novartis, Roche, Consultant of: Abbvie, Biogen, BMS, Celltrion, Gebro, Lilly, Mylan, Pfizer, Sandoz, Sanofi, Paid instructor for: Lilly, Speakers bureau: BMS, Lilly, Pfizer, Sandoz, Sanofi, Esther Ramirez: None declared